An exploratory research on the role of personality, values, and ideological attitudes on political choice of Filipinos during the 2022 Philippine presidential elections - Cruzabra, Bianca Ysabel T. (Animo Repository, 2022)
This study aims to examine if certain personality traits, values, and ideological attitudes predict political choice in the context of the 2022 Philippine Presidential Elections. A total number of 522 participants were included in the study. The measures included the Ten Item Personality Inventory, Dirty Dozen, Light Triad scale, Ten Item Values Inventory, Very Short Authoritarianism scale, and the Short Social Dominance Orientation scale. Logistic Regression using the backwards likelihood ratio method was used to analyze the data. Results have shown that individuals with higher levels of conscientiousness, psychopathy, faith in humanity, tradition, right-wing authoritarianism, and social dominance orientation have a higher chance of voting for Marcos and a lower chance of voting for Robredo; whereas individuals with higher levels of Machiavellianism, humanism, and achievement have a higher probability of voting for Robredo and a lower probability of voting for Marcos. The findings of this study have implications with regard to examining political behavior and political orientation in the Philippines.